Instilling The Value Of Tolerance Through Moderate Islamic Religious Education: A Pedagogical Approach In The Context Of Public Schools In Gresik - Septianingrum, Cindi; Arif, Muhamad; Mulyadi, Mulyadi (Tarbawi : Jurnal Pendidikan Islam, 2025)
This study aims to analyze the moderate Islamic Religious Education (PAI) learning model in fostering tolerant attitudes among students at UPT SMPN 16 Gresik, as well as to identify the challenges faced by teachers in implementing such models. The background of this research is based on the multicultural environment of the school, where teachers and students adhere to different beliefs, yet a conducive and tolerant learning atmosphere is maintained. This research employs a descriptive qualitative approach using a case study method. Data collection techniques include in-depth interviews, observation, and documentation, involving PAI teachers, non-PAI teachers, the curriculum vice principal, and students as research subjects. Data analysis follows Yin’s approach, involving pattern matching, explanation building, and time-series analysis, validated through source, method, and theory triangulation. The findings reveal that the learning models used by teachers are Problem-Based Learning and Cooperative Learning, with a student-centered approach and the use of questioning, discussion, and lecture techniques. Internal challenges include limited teacher understanding of tolerance-based education, while external challenges involve media influence and peer environments that may not align with tolerant values. Therefore, it is necessary to improve teacher competence through relevant training and ensure the involvement of parents and the surrounding community in supporting the development of students' tolerant attitudes.